THE DOMINANCE OF ALGORITHMIC CURATION AND THE WEAKENING OF CRITICAL THINKING ON SOCIAL MEDIA - Daeng Sani Ferdiannsyah; Amrina Rosada (Universitas Islam Negeri Mataram, 2026)
The development of social media has transformed the way society accesses and consumes information through algorithmic curation mechanisms. Several studies have shown that the dominance of algorithms influences critical thinking. This study employs a Systematic Literature Review (SLR) method by following the stages of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The findings indicate that algorithmic curation tends to strengthen content personalization, create filter bubbles and echo chambers, and limit users’ exposure to diverse information. This condition has implications for the decline in users’ ability to critically evaluate information. The dominance of algorithmic curation has a significant impact; therefore, strengthening digital literacy and promoting algorithmic transparency are necessary as mitigation efforts.